Cuiambuca gen. nov., a new genus of Sparianthinae spiders (Araneae: Sparassidae) from Brazil - Rheims, Cristina A. (European Journal of Taxonomy, 2023)
A new genus of Sparianthinae spiders, Cuiambuca gen. nov., is proposed to include the type species, Cuiambuca vacabrava sp. nov. (♂♀), from Paraíba and Sergipe, C. aratangi sp. nov. (♂♀), from Paraíba and Pernambuco, and C. borborema sp. nov. (♀) from Alagoas, all in northeastern Brazil. The genus is remarkable in that it exhibits a partly sclerotized conductor, with a sclerotized base and a distal hyaline sheath, in the male palp, a keyhole-shaped median septum in the female epigyne as well as a gourd-shaped spermathecae and blind ending projection in the vulva. All species are described and illustrated and a distribution map is provided.